Low dietary adherence after a positive food challenge in food allergic adults. Issue 2 (18th February 2022) - Versluis, Astrid; Le, Thuy‐My; Erp, Francine C. van; Blankestijn, Mark A.; Houben, Geert F.; Knulst, André C.; Os‐ Medendorp, Harmieke van
Abstract: Background: After a positive food challenge (FC), patients receive dietary advice regarding avoidance of the culprit food. We examined the frequency and variables associated with dietary adherence after a positive FC in adults. Methods: In this prospective daily practice study, adults with a positive FC were included. After every FC, dietary advice was given consisting of three options: (1) strict avoidance, (2) avoidance but products with precautionary allergen labelling (PAL) allowed and (3) (small) amounts allowed. Questionnaires about dietary adherence and associated variables were completed prior to and 6 months after the FC(s). Results: 41 patients (with 58 positive FCs) were included. Overall, patients adhered to the advised diet after 31% of the FCs. After 33 FCs, the advice was strict avoidance, whereof 82% followed a less strict diet. After 16 FCs, the advice was avoidance but products with PAL allowed, whereof 19% followed a less strict and 25% a stricter diet. In 9 FCs with the least strict advice, "(small) amounts allowed'', 67% followed a stricter diet. Three variables were associated with adherence: misremembering dietary advice, impaired health‐related quality of life (HRQL) on domain "Emotional impact'' and the need for dietary change after the FC. Conclusion: After one third of the positive FCs, patients adhered to the dietary advice. Variables associated with adherence were misremembering dietary advice,  impaired HRQL on domain "Emotional impact'' and the need for dietary change after the FC. It seems important that healthcare professionals should more frequently apply adherence‐enhancing strategies to improve dietary adherence.